Photoresponsive Covalent Organic Frameworks: Visible‐Light Controlled Conversion of Porous Structures and Its Impacts - Feng, Yu; Wang, Guangtong; Liu, Ruoyang; Ye, Xingyao; Tao, Shanshan; Addicoat, Matthew A.; Li, Zhongping; Jiang, Qiuhong; Jiang, Donglin (Angewandte Chemie International Edition, 2024)
Covalent organic frameworks are a novel class of crystalline porous polymers that enable molecular design of extended polygonal skeletons to attain well‐defined porous structures. However, construction of a framework that allows remote control of pores remains a challenge. Here we report a strategy that merges covalent, noncovalent, and photo chemistries to design photoresponsive frameworks with reversibly and remotely controllable pores. We developed a topology‐guided multicomponent polycondensation system that integrates protruded tetrafluoroazobenzene units as photoresponsive sites on pore walls at predesigned densities, so that a series of crystalline porous frameworks with the same backbone can be constructed to develop a broad spectrum of pores ranging from mesopores to micropores. Distinct from conventional azobenzene‐based systems, the tetrafluoroazobenzene frameworks are highly sensitive to visible lights to undergo high‐rate isomerization. The photoisomerization exerts profound effects on pore size, shape, number, and environment, as well as molecular uptake and release, rendering the system able to convert and switch pores reversibly and remotely with visible lights. Our results open a way to a novel class of smart porous materials with pore structures and functions that are convertible and manageable with visible lights. A new class of photoresponsive porous frameworks were created by integrating protruded tetrafluoroazobenzene units onto pore walls of 1D channels, constructing a broad spectrum of photoresponsive pores. The frameworks are highly sensitive to visible lights, convert pores into new ones via photoisomerization, and achieve benchmark changes in pore size, shape, number, and environment as well as gas uptake and release, opening a way to novel smart porous materials.